PENINGKATAN HASIL BELAJAR KETERAMPILAN MENYIMAK BAHASA JERMAN MENGGUNAKAN MEDIA KAHOOT SISWA KELAS XI SMA NEGERI 1 TARIK - Lomi, Fuxie Reinhard; Pujosusanto, Ari (LATERNE, 2023)
The results of the German listening skills of class XI IBB students at SMA Negeri 1 Tarik are classified as low. One explanation is the absence of purpose of media in learning and never even using the learning media. Learning just purposes books as a wellspring of advancing so it appears to be exhausting. To overcome this problem, we need to learn media. The use of learning media is very important because it can affect students learning outcomes. For this reason, Kahoot media is one of the media used in this research, because it has many unique features and is more varied and fun. The plan of the issue in this review is the means by which the aftereffects of mastering German listening abilities involving Kahoot media for class XI, understudies of SMA N 1 Tarik. The intended learning outcomes were obtained through a German listening skills test with the Family Theme. This study used a qualitative approach with a descriptive research type. The data from this study is the learning outcomes of class XI IBB students at SMA Negeri 1 Tarik before and after using Kahoot media. This exploration was led in 3 gatherings. In the first meeting, students were given materials and listening skills. The second meeting of learning was carried out using Kahoot media and in the third meeting the listening skill test was carried out. The outcomes showed that there was an expansion in listening skills, learning outcomes, before and after the test. This is shown frrom the averagee value of the initial class test which is equal to 54.6 and the final class test obtains an average value of 82.5.